In defence of "anecdotal data". A case study from a caribou area in West Greenland - Blehr, Otto (Rangifer, 1997)
The author pleads for a modification of ethological science that allows for the presentation of even tentative hypotheses, based on what is at present disparagingly referred to as "anecdotal data". It is argued that such data are crucial for the neglected study of the habituation of free-ranging large mammals. In such studies of learning, relevant behavioural observations lie outside the ethologist's control, and can only be replicated by further chance encounters. Observations in their anecdotal form should therefore be made available to other ethologists despite their lack of quantifiable data. This would allow for the creation of a pool of more or less unique observations helping to better understand behaviour.